Irony in the anti-poetry of Nicanor Parra - Reyes Calderón, Jaime Ricardo (2018)
The deviation from the norm is the foundation that structuralist theorists have proposed to define the sense of the poetic. As Jakobson affirms: “in reality poetic language makes an essential change in the relationships between the signifier and the meaning, as well as between the sign and the concept.” With this premise of backdrop, here we offer an approach to the anti-poetry of Nicanor Parra, who develops his poeticity against the norms of poetry itself. We perform a textual exercise of analysis and commentary from the antipoetic and irony, unraveling the divergences and critical emphases that emerge in the poetry records of the Chilean author who passed away in January 2018, guiding us through the socio-semiotic concepts of Bakhtin.